Investigation of localized surface plasmon/grating-coupled surface plasmon enhanced photocurrent in TiO2thin films - Supeera Nootchanat (2018)
We fabricated plasmonic gold nanoparticle (AuNP)-TiO 2 nanocomposite films and measured the photocurrent that originates from the water-splitting reaction catalyzed by the AuNP-TiO 2 nanocomposite photoelectrocatalytic (PEC) electrode. The localized surface plasmon resonance (LSPR) of the gold nanoparticles affected the generation of photocurrent by TiO 2 upon illumination with visible light. Electrochemical impedance spectroscopy (EIS) revealed that the improvement in the photocurrent generation originates from an enhancement in electron-hole pair generation induced by the SPR of the plasmonic gold nanoparticles rather than the extension of the electron lifetime. Mo reover, we introduced a novel method to enhance the photocurrent of TiO 2 by a multiple plasmonic effect, i.e., LSPR of plasmonic gold nanoparticles and the grating-coupled propagating SP on a gold grating. We fabricated the AuNP-TiO 2 nanocomposites on a gold-coated Blu-ray disc recordable (BD-R). The enhancement of the photocurrent due to the combination of LSPR and the grating-coupled SP was investigated. © the Partner Organisations 2014.